New distribution record of Varuna litterata from Caraga Region, Philippines: Analysis on morphometry, length/width-weight relationship, and condition factor (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Jumawan JH, Ruales JJJ, Avila MCA. 2022. New distribution record of Varuna litterata from Caraga Region, Philippines: Analysis on morphometry, length/width-weight relationship, and condition factor. Biodiversitas 23: 2935-2942. The study reported the occurrence of Varuna litterata in its habitat as a new record in Caraga Region, Philippines. The crab samples were collected using a hand-picked method and were of marketable sizes. There were 14 morphometric traits measured with the corresponding weight and sex of each specimen. Majority of the crab samples were medium-sized, with weight ranging from 11-20 grams, a carapace width range of 28-34 cm, and a carapace length range of 27-32 cm. Exploratory analysis of length /width-weight data fits the power regression model depicted into graphs. A strong relationship and highly significant was observed on pooled samples of WT-CW variables (R2: 0.9229: P
Keywords: Allometric growth, Fulton’s condition factor, Hubo River, regression model